Kinetics of Oxidation of 2,6-Diphenyltetrahydrothiopyran- 4-ones by Pyridinium Chlorochromate - Krishna Pillay, M.; Shanthi, R. (Asian Journal of Chemistry, 2010)
Oxidation of cis- and trans-isomers of 2,6-diphenyltetrahydrothiopyran-4-one by pyridinium chlorochromate are found to be first order in each with respect to [subs] and [oxd]. Rate has been found to increase with increase in acid concentration and the rate dependence on [H+] is not unity. Based on the kinetic results suitable mechanism has been proposed.